Characteristics and the Effect of Feldspar Reinforcement on Compression Strength Towards Various Types of Clay - Mohamad Nizam, Mohamad Zulfadhli; Ir. Dr. NORADILA BINTI ABDUL LATIF (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study use feldspar as a reinforcing material to investigate the compressive strength towards the various types of clay, in this case is SP17B, SP17C, SP22, and SP22B for application of sewage system, Vitrified Clay Pipes (VCP). The raw clay were dried, crushed to powder particle size (micro), sieved to ensure uniform size, compacted into cylinder shape, and sintered with control temperature at 1100⁰C with heating and cooling rate around 2 hours with a ramp of 2⁰C/min. Clay and feldspar powder is used to determine the material characterization of samples by EDS and TGA test. The results show that all of the materials has highest weight percentage of silicon (Si). Sintered sample will run a compression test, result in sample with 5% of feldspar show a signifciant improvement on compression force and strength, 2.63-5.66kN and 1.98-4.27 Mpa. Hence, the results obtained demonstrates feldspar’s potential as an economical and sustainable reinforcement to maximize VCP performance.